Activatable Cancer Sono‐Immunotherapy using Semiconducting Polymer Nanobodies. Issue 28 (6th June 2022) - Zeng, Ziling; Zhang, Chi; He, Shasha; Li, Jingchao; Pu, Kanyi
Abstract: Despite the great promises of sonodynamic therapy (SDT) in combination cancer therapy, its clinical applications are hindered by the "always‐on" pharmacological activities of therapeutic agents and the lack of efficient sonosensitizers. Herein, the development of semiconducting polymers as efficient sonosensitizers and further development of sono‐immunotherapeutic nanobodies (SPNAb ) for activatable cancer sono‐immunotherapy are reported. Conjugation of anti‐CTLA‐4 antibodies onto the polymer nanoparticles through a 1 O2 ‐cleavable linker affords SPNAb with relatively low CTLA‐4 binding affinity. Upon sono‐irradiation, SPNAb generates 1 O2 not only to elicit a sonodynamic effect to induce immunogenic cell death, but also to release anti‐CTLA‐4 antibodies and trigger in situ checkpoint blockade. Such a synergistic therapeutic action mediated by SPNAb modulates the tumoricidal function of T‐cell immunity by promoting the proliferation of cytotoxic T lymphocytes and depleting immunosuppressive regulatory T cells, resulting in effective tumor regression, metastasis inhibition, durable immunological memory, and prevention of relapse. Therefore, this study represents a proof‐of‐concept sonodynamic strategy using semiconducting polymers for precise spatiotemporal control over immunotherapy. Abstract : An activatable organic nanobody (SPNAb ) is developed for cancer sono‐immunotherapy. Ultrasound irradiation of SPNAb can not only induce immunogenic cell death by sonodynamic therapy but also activate anti‐CTLA4 antibodies to in situ trigger checkpoint blockade, resulting in enhanced systemic antitumor immunity.